Exploring the Professional Development Needs of Early Childhood Paraeducators and Supervising Teachers. (May 2022) - Frantz, Rebecca; Douglas, Sarah; Meadan, Hedda; Sands, Michelle; Bhana, Naima; D'Agostino, Sophia
Paraeducators play an important role supporting children with developmental disabilities in early childhood settings, and the current educational system has come to rely heavily on paraeducator supports. Unfortunately, most paraeducators receive limited training prior to engaging in their classroom roles and responsibilities, and teachers receive limited training related to supervising paraeducator staff. This study examined the roles and responsibilities, professional development experiences, perceived professional development needs, suggestions for professional development, and perceived barriers to professional development among early childhood paraeducators working with children with developmental disabilities and their supervising teachers using focus group method and a questionnaire. Implications for improving professional development practices among early childhood staff, remediating barriers to effective professional development, and future directions for research are discussed.